PROMOTING REFLECTIVE PRACTICE VIA THE USE OF 5-STEP COPORA REFLECTIVE MODEL: A CASE STUDY OF EAST MALAYSIAN ESL PRE-SERVICE TEACHERS - Ong, Wei Ann; Swanto, Suyansah; AlSaqqaf, Asmaa; Ong, Jia Wei (TEFLIN Journal, 2021)
Teachers who are reflective are found to be more able to develop themselves professionally. However, pre-service teachers were found to be in need of explicit instructions on reflective practice. This paper presents the results of an investigation on the use of the 5-step Cognition Practice Observation Reflection Action (CoPORA) reflective model among a group of Malaysian ESL pre-service teachers enrolled in an Institute of Teacher Education. A qualitative case study design was utilised, where the model was taught to a group of 13 pre-service ESL teachers who later completed the second phase of their teaching practice. The data for this study comprised the respondents' entries in their practicum reflection forms, reflective video blogs and focus group interviews. Results showed that respondents have moved from engaging in the lower levels of reflection to a higher pedagogical reflection. They also responded favourably to the use of the 5-step CoPORA reflective model for its structured approach. Nevertheless, the respondents lamented their struggles in rationalising issues faced and in suggesting suitable solutions. It is proposed that the pre-service teachers were shown exemplars of critical reflection to help them see the level at which they ought to reflect. Alternatively, teacher educators can explore a dialogic or collaborative approach to reflection so pre-service teachers can work with one another to further develop their reflective practice.